2019
DOI: 10.1104/pp.19.00954
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin Signaling Is Required for Far-Red Light-Induced Shoot Elongation in Pinus tabuliformis Seedlings

Abstract: Gibberellin (GA) is known to play an important role in low red/far-red (R:FR) light ratio-mediated hypocotyl and petiole elongation in Arabidopsis (Arabidopsis thaliana). However, the regulatory relationship between low R:FR and GAs remains unclear, especially in gymnosperms. To increase our understanding of the molecular basis of low R:FR-mediated shoot elongation in pines and to determine whether there is an association between low R:FR and GAs action, we explored the morphological and transcriptomic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…Although shade-avoidance responses are displayed by a wide variety of plant species representing a broad spectrum of growth forms, including wild and cultivated herbaceous plants (Ballare ét al., 1990;Pierik et al, 2004;Kebrom and Brutnell, 2007;Sasidharan et al, 2008;Whipple et al, 2011;Cagnola et al, 2012;Chitwood et al, 2015;Gommers et al, 2017;Molina-Contreras et al, 2019), grasses (Casal et al, 1985;Finlayson et al, 1998;Kebrom and Brutnell, 2007), vines (Izaguirre et al, 2013), and trees (Ritchie, 1997;de la Rosa et al, 1998;Li et al, 2020), in this section we focus mostly on what has been found in Arabidopsis, since this model provides the most advanced mechanistic insight into the topic. To maintain the focus of this review, we concentrate on the core pathways for shade avoidance that often crosstalk with defense.…”
Section: Molecular Mechanisms Of Light Signaling Toward Growth and Defensementioning
confidence: 99%
“…Although shade-avoidance responses are displayed by a wide variety of plant species representing a broad spectrum of growth forms, including wild and cultivated herbaceous plants (Ballare ét al., 1990;Pierik et al, 2004;Kebrom and Brutnell, 2007;Sasidharan et al, 2008;Whipple et al, 2011;Cagnola et al, 2012;Chitwood et al, 2015;Gommers et al, 2017;Molina-Contreras et al, 2019), grasses (Casal et al, 1985;Finlayson et al, 1998;Kebrom and Brutnell, 2007), vines (Izaguirre et al, 2013), and trees (Ritchie, 1997;de la Rosa et al, 1998;Li et al, 2020), in this section we focus mostly on what has been found in Arabidopsis, since this model provides the most advanced mechanistic insight into the topic. To maintain the focus of this review, we concentrate on the core pathways for shade avoidance that often crosstalk with defense.…”
Section: Molecular Mechanisms Of Light Signaling Toward Growth and Defensementioning
confidence: 99%
“…In the shade avoidance response, growth promotion under a low red/far-red light ratio was associated with enhanced expression of GA20ox genes in Arabidopsis petioles ( Hisamatsu et al. 2005 ), whereas in seedlings of the gymnosperm Pinus tabuliformis , under these conditions, KAO expression was strongly induced ( Li et al. 2020 ).…”
Section: Regulation Of Ga Metabolismmentioning
confidence: 99%
“…In forage crops such as Medicago truncatula GA is used to improve biomass production for land harnessing [ 231 ]. Shade avoidance response is a non-desirable trait in crops, but it may be modulated to increase wood production in Chinese red pine by means of specific GA treatment and light regimes [ 232 ]. Similarly, in hybrid poplar, the production of wood and biofuel can be increased by enhancing the expression of the GA biosynthesis gene GA20ox [ 233 ].…”
Section: Current and Potential Applicationsmentioning
confidence: 99%